Koncepcija kriticeskoj skorosti bega i ee ocenka u begunov na srednie distanci - Kryazhev, V. D.; Volodin, R. N.; Solovyov, V. B.; Skudnov, V. M. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
Critical running speed (Vcrit) is the lowest speed of achievement of the VO2max, which according to the mathematical model is observed on the 7th minute of running to exhaustion. The running time at the VO2 max level is limited and competitive running at distances requiring more than 7 minutes to overcome takes place at lower speeds. The smaller the speed reduction, the higher the endurance index. In theory, Vcrit is the ratioVO2max to running economy. Various terms: critical speed (Vcrit), maximum aerobic speed (Vamax), VO2max running speed (VVO2max) - denote the same concept. The study compared five different Methods of Vcrit assessment: The maximum speed achieved in a increasing test on a treadmill; at a critical and threshold speed ratio; Conconi test; fverage running speed at 3000 m; by Wandervalle equation, which is considered to be of theoretical value. It was revealed that the closest to the theoretical value of the Vcrit score on the result of running at 3000 m. For middle-skilled athletes, the bias error is 0.15m/s. For higher-skilled athletes, the Vcrit rating error is reduced.